MEDIATION AS AN EFFORT TO SETTLE INHERITANCE DISPUTES FROM THE LEGAL OBJECTIVE THEORY PERSPECTIVE (Study of Supreme Court Regulation Number 1 of 2016) - Ido Gustiawan Putra; Dominikus Rato; Dyah Ochtorina Susanti (Universitas Labuhanbatu, 2024)
This article analyzes Mediation in Supreme Court Regulation (PERMA) Number 1of 2016 as an effort by the Religious Court to resolve inheritance disputes from the perspective of legal purpose theory. The theory of legal purpose is used to see the content of legal certainty, justice, and benefit in PERMA Number 1 of 2016 which is the legal basis for Mediation of inheritance disputes. This research is a yuridical normative research of the library research type. The results of this study indicate that Mediation regulated by PERMA Number 1 of 2016 contains legal objectives in the form of certainty, justice, and legal benefits, so that Mediation must be implemented by the court as the first way to resolve inheritance disputes. Keywords: Mediation; PERMA Number 1 of 2016, Inheritance Dispute, Legal Objective Theory